2020
DOI: 10.2174/1871526519666190426153258
|View full text |Cite
|
Sign up to set email alerts
|

Colistin Induced Assortment of Antimicrobial Resistance in a Clinical Isolate of Acinetobacter baumannii SD01

Abstract: : Colistin was considered as one the most effective antibiotic against Acinetobacter baumannii, a widely-known opportunistic pathogen. In recent years, a number of colistin resistant strains have also been reported. This work is commenced to investigate the contribution of efflux pumps toward resistance to colistin-like cyclic polypeptide antibiotics, as the efflux pumps serve as the escape routes leading to drug-resistance. RNA was extracted from A. baumannii isolates cultured from samples procured by trachea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Moreover, mutations in pheS that encodes phenylalanine-tRNA ligase subunit alpha seem to play a role in colistin resistance [ 164 ]. Beyond the two aforementioned ABC transporters, and as stated before in text, overexpressed RND efflux pump MexAB-OprM correlates with colistin resistance [ 156 , 165 ].…”
Section: Resistance To Polymyxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, mutations in pheS that encodes phenylalanine-tRNA ligase subunit alpha seem to play a role in colistin resistance [ 164 ]. Beyond the two aforementioned ABC transporters, and as stated before in text, overexpressed RND efflux pump MexAB-OprM correlates with colistin resistance [ 156 , 165 ].…”
Section: Resistance To Polymyxinsmentioning
confidence: 99%
“…RND efflux pump MexAB-OprM consists of MexA (the membrane fusion protein), MexB (the carrier located in the inner membrane), and OprM (the transporter positioned in the outer membrane). MexAB-OprM associates with lack of susceptibility to most antibiotics, including trimethoprim and even colistin, when expressed in high levels [ 156 , 165 ]. As mentioned above in text, efflux pumps AdeIJK and LmrS confer resistance to trimethoprim [ 148 ].…”
Section: Resistance To Othersmentioning
confidence: 99%
“…OmpW has cytotoxic effect towards cells in the host that is implicated in innate tolerance to different ecological stressors. A. baumannii's OmpW mutation decreased adhesion production or hindered the bacterium's capacity to attach to as well as invade A549 cell [70][71]. Furthermore, another research utilizing a rodent intraperitoneal septic paradigm found that a deletion in OmpW had no impact in sensitivity to various medications.…”
Section: Ompwmentioning
confidence: 99%
“…Polymyxins (colistin and polymyxin B) are last-resort antibiotics reintroduced into clinical practice to treat infections caused by MDR Gram-negative bacteria resistant to carbapenems. Resistance to polymixins occurs due to mutations in chromosomal genes involved in lipopolysaccharide structure (mgrB, pmrABC, lpxACD), plasmid-mediated LPS modification (mcr genes), or active efflux [216][217][218][219][220][221][222][223].…”
Section: Polymyxin Resistancementioning
confidence: 99%